Subjective disgust and facial electromyography responses towards unedited and morphed overweight self‐pictures in women with varying levels of eating disorder symptomatology. (5th August 2022) - Masselman, Irina; de Jong, Peter J.; Glashouwer, Klaske A.
Abstract: Individuals with an eating disorder (ED) often report to be disgusted by their body. Body‐related self‐disgust could play an important role in the development and maintenance of EDs. We investigated if women with relatively high ED symptom scores indeed respond with disgust upon exposure to their body as indexed by facial electromyography (fEMG) of the m. levator labii superioris and self‐report. Given that one's self‐disgust may increase/decrease depending on the relative distance of the own body to the thin ideal, we also assessed women's disgust for overweight‐ and thin‐morphs of their body. Female undergraduate students ( N = 104) were photographed and presented with their (morphed) body pictures, next to disgust‐relevant and overweight body control pictures. Higher levels of ED symptoms were associated with stronger self‐reported disgust to unedited body‐pictures and overweight‐morphs. Disgust to thin‐morphs was unrelated to ED symptoms. Participants generally showed heightened facial disgust towards overweight morphs, yet the strength of facial disgust was unrelated to ED symptoms. Thus, the findings provide evidence for the involvement of heightened body‐related self‐disgust in ED symptomatology, albeit only on the basis of self‐report. Key points: Eating disorder symptoms were related to stronger subjective disgust to unedited and morphed overweight self‐pictures. This relationship was not evident for morphed underweight self‐pictures. Eating disorder symptoms were not associated with stronger fEMG activation to unedited and morphed self‐pictures.